The Social and Historical Context of the Mental Health Recovery Movement in the United States - Hao YAO (Yixue yu zhexue)
The mental health recovery movement originated in the United States during the 1990s, emphasizing person-centered, user-driven, and strengths-based approaches. It has become a significant force in shaping 21st-century global mental health policies. Through a systematic exploration of the movement, this article investigates its three primary socio-historical contexts: the progression in the understanding of recovery from severe mental illness, the evolution of the psychiatric consumer movement, and the development of psychosocial rehabilitation. It emphasizes the critical role of sustained reform efforts, the participation of individuals with lived experience of mental illness, the cultivation of professionals in mental health social work and clinical psychology, and further localized research on recovery in achieving the paradigm shift toward a recovery-oriented mental health system in China.